2017
DOI: 10.5664/jcsm.6694
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Non-Allergic Rhinitis Are Common in Obstructive Sleep Apnea but Not Associated With Disease Severity

Abstract: This study suggests that despite a comparatively high prevalence in patients with OSA, the presence or severity of AR or NAR does not influence the severity of OSA; however, rhinitis may significantly disturb sleep in patients with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
3
22
1
2
Order By: Relevance
“…By omitting one study each time using a random effects model, sensitivity analysis was conducted for meta-analyses of sleep duration, ESS score, AHI assessed by PSG, sleep efficiency assessed by PSG, the percentage of sleep stage REM assessed by PSG, nocturnal enuresis, restless sleep, OSA, snoring, and daytime sleepiness. Pooled results of sleep duration and AHI assessed by PSG were significantly sensitive to the study of Zheng et al [30], because the direction of the synthesized MD changed after it was omitted. The results of the ESS score, sleep efficiency evaluated by PSG, nocturnal enuresis, restless sleep, and daytime sleepiness also showed instability.…”
Section: Assessment Of Study Quality and Sensitivity Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…By omitting one study each time using a random effects model, sensitivity analysis was conducted for meta-analyses of sleep duration, ESS score, AHI assessed by PSG, sleep efficiency assessed by PSG, the percentage of sleep stage REM assessed by PSG, nocturnal enuresis, restless sleep, OSA, snoring, and daytime sleepiness. Pooled results of sleep duration and AHI assessed by PSG were significantly sensitive to the study of Zheng et al [30], because the direction of the synthesized MD changed after it was omitted. The results of the ESS score, sleep efficiency evaluated by PSG, nocturnal enuresis, restless sleep, and daytime sleepiness also showed instability.…”
Section: Assessment Of Study Quality and Sensitivity Analysismentioning
confidence: 89%
“…AR has been found to be positively associated with sleep-disordered breathing (SDB) [20], obstructive sleep apnea (OSA) [21], shorter sleep duration [22], poor sleep quality [23], sleep bruxism [24], night sweating [25], nocturnal enuresis [26], and daytime dysfunction [27]. However, these results are also controversial, since several studies found a negative or insignificant relationship between AR and the above sleep-related outcomes [7,[28][29][30]. Currently, there is a lack of systematic reviews to evaluate the association between AR and sleep pattern through meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some observational studies have shown how the nasal congestion induced by AR is an important factor in sleep impairment 121630 . One large population-based study involving about 5,000 adults demonstrated that individuals reporting frequent nasal congestion (5 nights/month) due to allergy were almost twice as likely to have moderate-to-severe SDB than individuals without nasal congestion due to allergy 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism through which AR causes poor quality of sleep and daytime fatigue is not entirely clear, but several factors are believed to be involved. Inflammatory mediators such as interferon- (IFN-) gamma, tumour necrosis factor- (TNF-) alpha, interleukin- (IL-) 1b, IL-4, IL-10, postural changes and certain therapeutic agents, such as antihistamines, may have a direct impact on sleep regulation 121316 .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep duration and insomnia may be additional factors affecting the relationship of OSA to sleepiness [6,9]. There is also increasing evidence that medical conditions that often coexist with OSA, such as CRS, anxiety, depression, PTSD and GERD, are associated with sleep complaints [11,12,13,14,15,16,17] and may confound the relationship between OSA and sleep-related quality of life outcomes. The independent contribution of each of these conditions to sleep-related complaints and the associated quality of life has not been closely examined.…”
Section: Introductionmentioning
confidence: 99%